Peran Kepala Madrasah dalam Pembinaan Professionalisme Guru MTsN 1 Kota Kediri - Ari Gunawan; Susiati Alwy (Universitas Islam Tribakti Lirboyo Kediri, 2021)
The purpose of this research is to find out the role of the madrasah head and the efforts made in coaching professional teachers. The research method uses a descriptive qualitative approach. The research location is MTsN 1 Kota Kediri. Data is obtained through primary sources and secondary sources. Data collection procedures are conducted through observation, documentation, interviews. The role of madrasah head leadership in professional coaching of teachers is as a manager, as a motivator, as a supervisor has been done by the head of the madrasah in MTsN 1 Kota Kediri. While the efforts made in professional coaching teachers are forming MGMP, forming PKG, holding SKP, conducting training every completed 60 hours teaching to train and develop the profession of teachers as professional educators in teaching students.